Treatment Patterns of Long-Acting Somatostatin Analogs for Neuroendocrine Tumors - Callisia N. Clarke; Paul Cockrum; Thomas J.R. Beveridge; Michelle Jerry; Donna McMorrow; Anh Thu Tran; Alexandria T. Phan (Journal of Health Economics and Outcomes Research)
**Background:** Long-acting somatostatin analog therapy (LA-SSA) is recommended as first-line therapy for treatment of unresectable or metastatic neuroendocrine tumors (NETs). Understanding treatment sequencing and dosing patterns of LA-SSA is essential for clinical decision-making to provide value-based management of NETs.